2009
DOI: 10.1097/jgp.0b013e3181ab8b36
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Growth, Social Acknowledgment as Survivors, and Sense of Coherence in Former German Child Soldiers of World War II

Abstract: Objectives: To examine posttraumatic growth and its predictors social acknowledgment as survivors, sense of coherence, trauma severity, and further factors in former child soldiers more than 60 years after deployment. Design: Cross-sectional. Setting: University-based geropsychiatric center in Germany. Participants: 103 former German child soldiers of World War II, mean age 78 years, 96% experienced at least one war trauma. Measurement: Subjects completed the Posttraumatic Growth Inventory (PTGI), Social Ackno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 41 publications
(73 reference statements)
6
61
1
Order By: Relevance
“…Consistent with results from Sommer et al (2017b), general disapproval was not only related to more severe PTSD symptoms (Forstmeier, Kuwert, Spitzer, Freyberger, & Maercker, 2009) but also negatively related to changes in PTSD after treatment and over time. This is in line with findings by Xu et al (2015) indicating that a positive change in social acknowledgment is associated with reduced PTSD after treatment.…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with results from Sommer et al (2017b), general disapproval was not only related to more severe PTSD symptoms (Forstmeier, Kuwert, Spitzer, Freyberger, & Maercker, 2009) but also negatively related to changes in PTSD after treatment and over time. This is in line with findings by Xu et al (2015) indicating that a positive change in social acknowledgment is associated with reduced PTSD after treatment.…”
Section: Discussionsupporting
confidence: 83%
“…The results of a study by Kuwert et al (2008), which looked at a group of former World War II child soldiers and the possible influence of a sense of coherence in coping with war experiences, underpin this presumption. Forstmeier et al (2009) found that the most important predictors for post-traumatic growth among former child soldiers from World War II were social recognition as survivors and an increased sense of coherence. Viewed from a resourceoriented perspective, future studies should pay special attention to the psychosocial adaptations that are being activated by the elderly and the important therapeutic approaches that could result from this.…”
Section: War-related Traumamentioning
confidence: 99%
“…3 In theory, combat exposure could have either a positive or negative effect on postdeployment violence. Exposure to combat is often described by mental health experts as the trigger for, or indirectly leading to, acts of violence committed upon returning home (Grossman et al 2008;Killgore et al 2008;Songtag and Alvarez 2008;Elbogen et al 2012a;MacManus et al 2012;MacManus et al 2013;Sreenivasan et al 2013), but previous studies have found that exposure to adversity, including combat, can result in "post-traumatic growth" (Elder and Clipp 1989;Fontana and Rosenheck 1998;Koenig et al 1998;McMillen and Cook 2003;Dohrenwend et al 2004;Maguen et al 2006;Forstmeier et al 2009). Several features of post-traumatic growth (e.g., increased compassion, self-discipline, resilience, and spirituality) could reduce the propensity to engage in violent behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Although exposure to combat is often described as the trigger for acts of violence committed upon returning home (Killgore et al 2008;Songtag and Alvarez 2008;Elbogen et al 2012a;Sreenivasan et al 2013), there is also evidence that it can result in increased compassion, self-discipline, resilience, and spirituality (Elder and Clipp 1989;Fontana and Rosenheck 1998;Dohrenwend et al 2004;Maguen et al 2006;Forstmeier et al 2009), all of which could potentially reduce the propensity to engage in violent behavior.…”
mentioning
confidence: 99%